PERAN DAN TUGAS RECEPTIONIST PADA PT. SERIM INDONESIA - Nani Nuraini Sarah; Ayu Putri Utari (Jurnal Sekretari Universitas Pamulang, 2016)
AbstractReaching a Qualified Receptionist.(This paper is excerpted from the final project report entitled ‘The Role and Tasks of Receptionist in PT Serim Indonesia)            It is very usual if we walk-in an office, we are greeted by someone who is known as receptionist. A receptionist is an employee taking an office/administrative support position. The work is usually performed in a waiting area such as a lobby orfront office desk of an organization or business. The title "receptionist" is attributed to the person who is employed by an organization to receive orgreet any visitors, patients, or clients and answer telephone calls. Many small-to-large-sized business owners need receptionists for supporting their office activities.The aim of this present paper is to explore the receptionists’ jobs and the criteria to become qualified ones. As they are the front line that directly deal with customers, they must demonstrate their professionalism, such as courtesy, and making sure that customers are feeling welcome on their visiting experience.Nowadays, even when the advancement of office automation has eliminated some receptionists' jobs. (e.g: a telephone call could be answered by an automated attendant). A receptionist who possesses strong office/technical skills and who is also adept in courtesy, tact and diplomacy is still considered an asset to a company's business image, and is still very much in demand in the business world.Kata kunci: Receptionist, petugas kantor depan , staf administrasi.